REKA KAIN FELT SEBAGAI MEDIA BEREKSPRESI SENI SERAT - Panji Kurnia Nugraha, - (2019)
ABSTRACT Panji Kurnia Nugraha 2019. Fabrication of Felt Fabric as a Media for Expressing Fiber Art. Department of Fine Arts Education, Faculty of Art and Design, Indonesian University of Education. Felt or felt art was chosen by the writer as an exploration effort by raising the theme of Tanjung Tinggi Belitung beach. This beach has a unique beauty and characteristics, namely white sand with large rocks. The author creates three pieces of work with shades of beach sand, seawater, and rocks found on the beach. The stages of creation start from the preparation of yarn fibers according to the concept, then the giving of cornflour or maize mixture, after that the drying process and the last process is the finishing process. In the three works of the author, there is dry marine biota which the writer took directly from the shore so that his natural impression is maintained. Hopefully, the creation of writers' creation can be an inspiration for creating art with new media and techniques. Panji Kurnia Nugraha 2019. Reka Kain Felt Sebagai Media Berekspresi Seni Serat. Departemen Pendidikan Seni Rupa, Fakultas Seni dan Desain, Universitas Pendidikan Indonesia. Felt atau felt art dipilih penulis sebagai upaya ekplorasi dengan mengangkat tema pantai Tanjung Tinggi Belitung. Pantai ini memiliki keindahan dan ciri khas yang unik yaitu pasir putih dengan bebatuan yang besar. Penulis menciptakan tiga buah karya dengan nuansa pasir pantai, air laut, serta bebatuan yang terdapat di pantai tersebut. Tahapan penciptaan dimulai dari penyusunan serat benang sesuai konsep, kemudian pemberian adonan tepung jagung atau mayzena, setelah itu proses penjemuran dan proses terakhir yaitu proses finishing. Pada ke tiga karya penulis terdapat biota laut kering yang penulis ambil langsung dari bibir pantai agar kesan naturalnya terjaga. Semoga dengan terciptanya karya penciptaan penulis bisa menjadi inspirasi untuk berkarya seni dengan media dan teknik baru. Keywords: Textile Art, Felting, Felt Art, Tanjung Tinggi Beach, Belitung Island.